The prevalence of musculoskeletal disorders among undergraduates and technicians of operating room of the educational hospitals affiliated with Iran University of Medical Sciences in 2016 - Fariba Nasiri-Ziba; Sohrab Nosrati; Sedigheh Hanani (Tehran University of Medical Sciences, 2017)
Background & Aim: Musculoskeletal diseases are accounted for a major part of occupational diseases, which threaten the health and performance of medical staff, especially operating room nurses. Considering the importance of this matter, the aim of the present study was to determine the prevalence of musculoskeletal disorders among operating room nurses in educational hospitals affiliated with Iran University of medical Sciences in 2016. Methods & Materials: The present study was a descriptive analytical study. The samples for the present study were 133 operating room nurses who were selected using census sampling method. Data were gathered using Nordic Musculoskeletal Questionnaire and a researcher-made questionnaire and analyzed using independent t-test, chi square test and SPSS software version 22. Results: Results showed that the prevalence of musculoskeletal disorders during the past 12 months was 41.4% in the neck, 34.3% in the shoulders, 11.3% in the elbows, 35.3% in the wrists, 42.1% in the back, 61.7% in the waist, 16.5% in the buttocks, 46.6% in the knees and 29.3% in the feet. Results of chi square test showed a significant relation between the field of surgery and the prevalence of musculoskeletal disorders (p = 0.047). Independent t-test revealed a significant relation between the working history and occurrence of musculoskeletal disorders (p = 0.002). Conclusion: Results revealed the high prevalence of musculoskeletal disorders among operating room nurses and so, it is recommended to provide educational courses for teaching the principles of ergonomics and correct method of standing and also, Regulations for decreasing the working hours of the personnel.